Trucks off the Road: A Method for Assessing Economical Reductions of Logistical Requirements at Contingency Base Camps. Issue 2 (2nd April 2016) - Putnam, Nathaniel H.; Kinnevan, Kurt J.; Webber, Michael E.; Seepersad, Carolyn C.
Abstract: The U.S. Department of Defense has recently shown an interest in incorporating the concepts of energy efficiency and energy security into decision-making processes, including decisions that pertain to military base camp equipment. Logistics—transportation of resources to forward locations in a military context—make up the vast majority of costs associated with base camp resource use, but costs vary widely according to operational factors. Changing costs of resources affects cost-benefit analyses of resource-saving devices, confounding decision-making processes. A method for volumetric accounting is proposed, described, and demonstrated in this article through an example design problem, yielding metrics that engineering managers can use to effectively compare the benefits of resource-saving equipment without requiring quantification of money-saving potential. The metrics and method proposed in this analysis complement existing measures and have the potential to streamline certain decision-making processes, leading to more efficient, effective, and economical military base camps while also taking resource resupply convoys off dangerous roads.